Packaging adhesive suitable for high-speed cigarette making machine equipment and preparation method of packaging adhesive

By adopting packaging glue with specific ingredients and preparation methods, the existing cigarette packaging glue has solved the problems of uneven adhesion, excessive curing time and poor adhesion in high-speed cigarette machine equipment, fast curing and high adhesion are achieved, and production efficiency and packaging stability are improved.

CN119552596APending Publication Date: 2025-03-04ZHENGZHOU SHENHUO JIAOJI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411734236.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When existing cigarette packaging glue is used in high-speed cigarette machine equipment, there are problems such as uneven adhesion, excessive curing time and poor adhesion, resulting in unsolid packaging and low production efficiency.

Method used

Packaging glue consisting of chitosan modified acrylate polyvinyl alcohol, polyurethane, hydroxyethyl cellulose, sodium dodecyl sulfate and other components is used to improve the adhesive performance and curing speed of the glue through specific preparation methods and component ratios.

Benefits of technology

It realizes fast curing time and high adhesion of packaging glue, and is suitable for high-speed cigarette machine equipment, improves production efficiency and packaging stability, and avoids glue splashing and nozzle clogging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives for cigarettes, in particular to a packaging adhesive suitable for high-speed cigarette making machine equipment and a preparation method of the packaging adhesive. The packaging adhesive suitable for the high-speed cigarette making machine equipment is prepared from the following components in percentage by weight: 10 to 15 percent of chitosan modified acrylic acid esterified polyvinyl alcohol, 2 to 5 percent of polyurethane, 2 to 5 percent of hydroxyethyl cellulose, 1 to 3 percent of lauryl sodium sulfate, 0.5 to 1 percent of benzalkonium chloride, 0.5 to 1 percent of benzoyl peroxide, 1 to 2 percent of aluminum chloride, 0.5 to 1 percent of potassium sorbate and the balance of water. 0.5 to 1 percent of 3-bromine-9H-xanthene-9-ketone, 1 to 2 percent of corn starch and 65 to 75 percent of VAE (Vinyl Acetate Ethylene) water-based emulsion; the curing agent is high in curing speed and suitable for a high-efficiency cigarette production line. Along with evaporation of water after coating, a stable bonding layer can be formed in a short time, and the production efficiency and the automation level of a production line are improved; meanwhile, the adhesive force is high, the phenomenon that produced small boxes and strip-shaped boxes are not firmly adhered in the production process is avoided, and the phenomena that glue splashes and a nozzle is blocked are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives for cigarettes, and in particular to a packaging adhesive suitable for high-speed cigarette making machines and a preparation method thereof. Background Art

[0002] Cigarette machine packaging glue, as an adhesive specially used for packaging and packaging in cigarette production, the earliest cigarette packaging glue is usually made of natural rubber or starch-based adhesive. Early cigarette packaging glue was mainly used to seal the edges of packaging paper and seal the opening of cigarette packaging bags. Due to the low requirements for environmental protection and production efficiency at that time, the composition of these adhesives was relatively simple and mainly relied on traditional chemical methods. With the gradual mechanization of cigarette production, especially the popularity of high-speed cigarette machines and packaging machines, the traditional manual packaging method has been gradually replaced by automated production. Mechanized production requires more efficient and stable packaging glue that can quickly and firmly complete the packaging task on a high-speed production line. Therefore, the requirements for adhesive bonding performance, drying time, environmental protection, etc. have gradually become more stringent.

[0003] Chinese patent publication number CN102031075B discloses an environmentally friendly and energy-saving cigarette glue and a production method thereof. During use, the adhesive force is uneven, and sometimes the sealing is not firm, resulting in package damage or glue overflow, which in turn affects the integrity and appearance of the package. Chinese patent publication number CN1 17384570A discloses a multi-purpose water-based high-speed packaging glue and a preparation method thereof. During use, the adhesive has the problems of long curing time and poor adhesion.

[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a packaging adhesive suitable for high-speed cigarette making machine equipment and a preparation method thereof, which has the characteristics of fast curing time and high adhesion.

[0006] To achieve the above purpose, the present invention adopts the following technical scheme: a packaging adhesive suitable for high-speed cigarette making machine equipment is composed of the following percentage components: 10-15% chitosan modified acrylated polyvinyl alcohol, 2-5% polyurethane, 2-5% hydroxyethyl cellulose, 1-3% sodium dodecyl sulfate, 0.5-1% benzalkonium chloride, 0.5-1% benzoyl peroxide, 1-2% aluminum chloride, 0.5-1% potassium sorbate, 0.5-1% 3-bromo-9H-xanthene-9-one, 1-2% corn starch and 65-75% VAE aqueous emulsion;

[0007] The preparation method of chitosan modified acrylated polyvinyl alcohol comprises the following steps:

[0008] A1: Add acrylic acid into deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, stir at a temperature of 45-60°C and a stirring rate of 500-600 rpm for 30 minutes to completely dissolve the acrylic acid to obtain intermediate A;

[0009] A2: Add polyvinyl alcohol into deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, stir at a temperature of 60-72°C and a stirring rate of 500-600 rpm for 30 minutes to completely dissolve the polyvinyl alcohol to obtain intermediate B;

[0010] A3: Add intermediate A and intermediate B into a three-necked flask equipped with a serpentine condenser, a thermometer and a magnetic stirrer, adjust the inclination of the three-necked flask to 15-20°, turn on the condenser, adjust the reaction temperature of the three-necked flask to 85-90°C, set the speed of the magnetic stirrer to 800-1000rpm, condense and reflux for 90-120min, and then cool the reaction product to room temperature to obtain intermediate C;

[0011] A4: Transfer intermediate C to a high-pressure reactor, use inert gas (nitrogen) to increase the pressure and protect, adjust the reaction pressure to 1.3-1.6atm, then add chitosan and 1,2-hexyl isocyanate, adjust the speed of the magnetic stirrer in the reactor to 600-800rpm, adjust the reaction temperature to 60-65°C, stir the reaction at high pressure and high temperature for 60-90min, and after the reaction is completed, cool the reaction product to room temperature to obtain chitosan-modified acrylated polyvinyl alcohol.

[0012] Furthermore, in step A1, the mass ratio of acrylic acid to deionized water is 2:3; in step A2, the alcoholysis degree of polyvinyl alcohol is 85-90%, the polymerization degree is 500-600, wherein the mass ratio of polyvinyl alcohol to deionized water is 2:3; in step A3, the mass ratio of intermediate A to intermediate B is 1:1; in step A4, the mass ratio of intermediate C, chitosan and 1,2-hexyl isocyanate is 4:2:1.

[0013] Furthermore, a method for preparing packaging adhesive suitable for high-speed cigarette making machine equipment comprises the following steps:

[0014] B1: Preparation of chitosan-modified acrylated polyvinyl alcohol;

[0015] B2: polyurethane, chitosan-modified acrylated polyvinyl alcohol, hydroxyethyl cellulose and corn starch were added into the reaction kettle, the reaction temperature was adjusted to 45-60°C, the speed of the magnetic stirrer was set to 800-1000 rpm and stirred for 30 min, then aluminum chloride was added and the stirring reaction was continued for 1 h;

[0016] B3: Sodium lauryl sulfate, benzalkonium chloride, benzoyl peroxide, and potassium sorbate were added into the reaction kettle, the temperature was adjusted to 45-60°C, the speed of the magnetic stirrer was set to 1500-1800 rpm and stirred for 15 min;

[0017] B4: Add 3-bromo-9H-xanthene-9-one and VAE aqueous emulsion into a reaction kettle, adjust the reaction temperature to 75-80°C, set the speed of the magnetic stirrer to 800-1000 rpm, and stir for 30 minutes to obtain a packaging adhesive suitable for high-speed cigarette making equipment.

[0018] Furthermore, the hydroxyethyl cellulose is water-soluble hydroxyethyl cellulose with a density of 7000-9000 g / cm 3 ; The VAE aqueous emulsion is a modified VAE emulsion with a viscosity of 500-600mPa·S.

[0019] In summary, due to the adoption of the above technical solution, the beneficial effect of the present invention is that the curing speed of the present invention is fast and suitable for a high-efficiency cigarette production line. As the water evaporates after coating, the present invention can form a stable adhesive layer in a short time, improving the production efficiency and the automation level of the production line; at the same time, the present invention has strong adhesion, and the small boxes and strip boxes produced will not be loosely adhered during the production process, and there will be no glue splashing and nozzle clogging. DETAILED DESCRIPTION

[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0021] The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0022] Example 1

[0023] 1: Add 200 g of acrylic acid into 300 ml of deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, and stir at 60°C and 600 rpm for 30 min to completely dissolve the acrylic acid to obtain intermediate A;

[0024] 2: Add 200 g of polyvinyl alcohol into 300 ml of deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, and stir at 72°C and a stirring rate of 600 rpm for 30 min to completely dissolve the polyvinyl alcohol to obtain intermediate B;

[0025] 3: Add intermediate A and intermediate B to a three-necked flask equipped with a serpentine condenser, a thermometer and a magnetic stirrer, adjust the inclination of the three-necked flask to 20°, turn on the condenser, adjust the reaction temperature of the three-necked flask to 90°C, set the speed of the magnetic stirrer to 1000 rpm, condense and reflux for 120 minutes, and then cool the reaction product to room temperature to obtain 800 ml of intermediate C;

[0026] 4: Transfer intermediate C to a high-pressure reactor, use inert gas (nitrogen) to increase the pressure and protect, adjust the reaction pressure to 1.6 atm, then add 400 g of chitosan and 200 ml of 1,2-hexyl isocyanate, adjust the speed of the magnetic stirrer in the reactor to 800 rpm, adjust the reaction temperature to 65°C, and stir the reaction at high pressure and high temperature for 90 minutes. After the reaction is completed, cool the reaction product to room temperature to obtain Example 1.

[0027] Table 1, reagent parameters used in Example 1

[0028]

[0029]

[0030] Example 2

[0031] 1: Add 80 g of acrylic acid into 120 ml of deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, and stir at 57°C and a stirring rate of 600 rpm for 30 min to completely dissolve the acrylic acid to obtain intermediate A;

[0032] 2: Add 80g of polyvinyl alcohol to 120ml of deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, and stir at 68°C and 600rpm for 30min to completely dissolve the polyvinyl alcohol to obtain intermediate B;

[0033] 3: Add intermediate A and intermediate B to a three-necked flask equipped with a serpentine condenser, a thermometer and a magnetic stirrer, adjust the inclination of the three-necked flask to 15°, turn on the condenser, adjust the reaction temperature of the three-necked flask to 88°C, set the speed of the magnetic stirrer to 1000 rpm, condense and reflux for 120 minutes, and then cool the reaction product to room temperature to obtain 320 ml of intermediate C;

[0034] 4: Transfer intermediate C to a high-pressure reactor, use inert gas (nitrogen) to increase the pressure and protect, adjust the reaction pressure to 1.5 atm, then add 160 g of chitosan and 80 ml of 1,2-hexyl isocyanate, adjust the speed of the magnetic stirrer in the reactor to 800 rpm, adjust the reaction temperature to 65°C, and stir the reaction at high pressure and high temperature for 90 minutes. After the reaction is completed, cool the reaction product to room temperature to obtain Example 2.

[0035] Table 2, reagent parameters used in Example 2

[0036]

[0037]

[0038] Example 3

[0039] 1: 10 g of polyurethane, 30 g of Example 1, 10 g of hydroxyethyl cellulose and 4 g of corn starch were added to a reactor, the reaction temperature was adjusted to 60°C, the speed of the magnetic stirrer was set to 1000 rpm and stirred for 30 min, then 4 g of aluminum chloride was added and the reaction was continued under stirring for 1 h;

[0040] 2: Add 6g sodium dodecyl sulfate, 2g benzalkonium chloride, 2g benzoyl peroxide and 2g potassium sorbate into the reactor, adjust the temperature to 60°C, set the magnetic stirrer speed to 1800rpm and stir for 15min;

[0041] 3: Add 2 g of 3-bromo-9H-xanthene-9-one and 130 ml of VAE aqueous emulsion into a reaction kettle, adjust the reaction temperature to 80° C., set the speed of the magnetic stirrer to 1000 rpm, and stir for 30 min to obtain Example 3.

[0042] Table 3, reagent parameters used in Example 3

[0043] Drug Name source model parameter Polyurethane Jinan Mingwei New Materials Co., Ltd. 060 1kg Hydroxyethyl Cellulose Sichuan Lanyang Daily Chemical Co., Ltd. XH-666 1kg Corn starch Jinan Xuzhou Chemical Co., Ltd. XZ-123 1kg Sodium Lauryl Sulfate Langfang Pengcai Chemical Co., Ltd. 151-21-3 25kg Benzalkonium chloride Aladdin A194586 100g Benzoyl peroxide Aladdin B104632 100g Potassium Sorbate Henan Jianchang Chemical Co., Ltd. 012 1kg 3-Bromo-9H-xanthene-9-one Aladdin B405461 5g VAE water-based emulsion Shandong Xinbaihe Chemical Co., Ltd. BJ-707 50kg

[0044] Example 4

[0045] 1: 4 g of polyurethane, 20 g of Example 2, 4 g of hydroxyethyl cellulose and 2 g of corn starch were added to a reactor, the reaction temperature was adjusted to 60° C., the speed of the magnetic stirrer was set to 1000 rpm and stirred for 30 min, then 4 g of aluminum chloride was added and the stirring reaction was continued for 1 h;

[0046] 2: Add 4g sodium dodecyl sulfate, 1g benzalkonium chloride, 1g benzoyl peroxide and 1g potassium sorbate into the reactor, adjust the temperature to 58°C, set the magnetic stirrer speed to 1800rpm and stir for 15min;

[0047] 3: Add 2 g of 3-bromo-9H-xanthene-9-one and 150 ml of VAE aqueous emulsion into a reaction kettle, adjust the reaction temperature to 80° C., set the speed of the magnetic stirrer to 1000 rpm, and stir for 30 min to obtain Example 4.

[0048] Table 4, reagent parameters used in Example 4

[0049] Drug Name source model parameter Polyurethane Jinan Mingwei New Materials Co., Ltd. 060 1kg Hydroxyethyl Cellulose Sichuan Lanyang Daily Chemical Co., Ltd. XH-666 1kg Corn starch Jinan Xuzhou Chemical Co., Ltd. XZ-123 1kg Sodium Lauryl Sulfate Langfang Pengcai Chemical Co., Ltd. 151-21-3 25kg Benzalkonium chloride Aladdin A194586 100g Benzoyl peroxide Aladdin B104632 100g Potassium Sorbate Henan Jianchang Chemical Co., Ltd. 012 1kg 3-Bromo-9H-xanthene-9-one Aladdin B405461 5g VAE water-based emulsion Shandong Xinbaihe Chemical Co., Ltd. BJ-707 50kg

[0050] Comparative Example 1

[0051] Example 3 of Chinese patent publication number CN1 17384570A was selected as comparative example 1.

[0052] Comparative Example 2

[0053] The embodiment of the Chinese patent with publication number CN102031075B was selected as comparative example 2.

[0054] Physical performance test:

[0055] The conventional performance parameters of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were subjected to physical performance tests: cotton cloth was selected as the test substrate, and the peel strength of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 was tested after being coated on the cotton cloth substrate for 30 seconds; the dilution stability was tested according to the high-speed cigarette adhesive dilution stability test method specified in "YC / T188-2004 High-speed Cigarette Adhesive", and the shear thinning index was tested according to the method of "Testing the Rheological Properties of Non-Newtonian Materials by Rotational Viscometer" specified in Appendix B of "ASTM D2196-2015 Standard Test Method" for Example 3, Example 4, Comparative Example 1 and Comparative Example 2;

[0056] Table 5, conventional physical properties test results:

[0057] Viscosity (mPa·S) Solid content (%) pH Dry time Example 3 300 48.5 4.7 6 minutes 30 seconds Example 4 300 48.9 4.7 6 minutes 45 seconds Comparative Example 1 300 50.6 4.7 8 minutes 15 seconds Comparative Example 2 400 52.4 4.8 6 minutes 12 seconds

[0058] Table 6, Physical properties test results

[0059]

[0060] On-machine performance test:

[0061] The cigarette machine packaging adhesives prepared in Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were tested on a machine:

[0062] Machine speed Roller coating Spraying Nozzle diameter Example 3 ≥600 packs / min Applicable Applicable <0.4mm Example 4 ≥600 packs / min Applicable Applicable <0.4mm Comparative Example 1 ≥600 packs / min Applicable Applicable <0.4mm Comparative Example 2 ≥600 packs / min not applicable Applicable <0.4mm

[0063] In the normal production process, the packaging glue prepared by Example 3 runs stably during the 8-hour production process, and the small boxes and strip boxes produced are firmly adhered, and there is no glue splashing or nozzle clogging during the operation process. After shutdown, there is a small amount of glue at the nozzle mouth; the packaging glue prepared by Example 4 runs stably during the 8-hour production process, and the small boxes and strip boxes produced are firmly adhered, and there is no glue splashing or nozzle clogging during the operation process. After shutdown, there is no glue formation at the nozzle mouth, and it is clean and free of dirt; the packaging glue prepared by Comparative Example 1 runs stably during the 8-hour production process, and the small boxes and strip boxes produced are firmly adhered, and a small amount of glue splashing occurs during the operation process. The nozzle is not clogged, and after shutdown, the nozzle has partial glue formation; the packaging glue prepared by Comparative Example 2 has nozzle clogging in about 4 hours during the production process, and glue falls off during the roller coating process, and the small boxes and strip boxes produced are partially not firmly adhered and fall off.

[0064] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A packaging adhesive suitable for high-speed cigarette making machines, characterized in that: The invention is composed of the following percentage components: 10-15% chitosan modified acrylated polyvinyl alcohol, 2-5% polyurethane, 2-5% hydroxyethyl cellulose, 1-3% sodium dodecyl sulfate, 0.5-1% benzalkonium chloride, 0.5-1% benzoyl peroxide, 1-2% aluminum chloride, 0.5-1% potassium sorbate, 0.5-1% 3-bromo-9H-xanthene-9-one, 1-2% corn starch and 65-75% VAE aqueous emulsion; The preparation method of chitosan modified acrylated polyvinyl alcohol comprises the following steps: A1: Add acrylic acid into deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, stir at a temperature of 45-60°C and a stirring rate of 500-600 rpm for 30 minutes to completely dissolve the acrylic acid to obtain intermediate A; A2: Add polyvinyl alcohol into deionized water, heat in a three-necked flask with a thermometer and a magnetic stirrer at an angle of 30°, stir at a temperature of 60-72°C and a stirring rate of 500-600 rpm for 30 minutes to completely dissolve the polyvinyl alcohol to obtain intermediate B; A3: Add intermediate A and intermediate B into a three-necked flask equipped with a serpentine condenser, a thermometer and a magnetic stirrer, adjust the inclination of the three-necked flask to 15-20°, turn on the condenser, adjust the reaction temperature of the three-necked flask to 85-90°C, set the speed of the magnetic stirrer to 800-1000rpm, condense and reflux for 90-120min, and then cool the reaction product to room temperature to obtain intermediate C; A4: Transfer intermediate C to a high-pressure reactor, use inert gas (nitrogen) to increase the pressure and protect, adjust the reaction pressure to 1.3-1.6atm, then add chitosan and 1,2-hexyl isocyanate, adjust the speed of the magnetic stirrer in the reactor to 600-800rpm, adjust the reaction temperature to 60-65°C, stir the reaction at high pressure and high temperature for 60-90min, and after the reaction is completed, cool the reaction product to room temperature to obtain chitosan-modified acrylated polyvinyl alcohol.

2. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: In step A1, the mass ratio of acrylic acid to deionized water is 2:

3.

3. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: In step A2, the alcoholysis degree of polyvinyl alcohol is 85-90%, the polymerization degree is 500-600, and the mass ratio of polyvinyl alcohol to deionized water is 2:

3.

4. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: The mass ratio of intermediate A to intermediate B in step A3 is 1:

1.

5. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: In step A4, the mass ratio of intermediate C, chitosan and 1,2-hexyl isocyanate is 4:2:

1.

6. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: The hydroxyethyl cellulose is water-soluble hydroxyethyl cellulose with a density of 7000-9000g / cm 3 .

7. The packaging adhesive suitable for high-speed cigarette making machine according to claim 1, characterized in that: The VAE aqueous emulsion is a modified VAE emulsion with a viscosity of 500-600 mPa·S.

8. The method for preparing packaging adhesive suitable for high-speed cigarette making machines according to claim 1, characterized in that: The following steps are involved: B1: Preparation of chitosan-modified acrylated polyvinyl alcohol; B2: polyurethane, chitosan-modified acrylated polyvinyl alcohol, hydroxyethyl cellulose and corn starch were added into the reaction kettle, the reaction temperature was adjusted to 45-60°C, the speed of the magnetic stirrer was set to 800-1000 rpm and stirred for 30 min, then aluminum chloride was added and the stirring reaction was continued for 1 h; B3: Sodium lauryl sulfate, benzalkonium chloride, benzoyl peroxide, and potassium sorbate were added into the reaction kettle, the temperature was adjusted to 45-60°C, the speed of the magnetic stirrer was set to 1500-1800 rpm and stirred for 15 min; B4: Add 3-bromo-9H-xanthene-9-one and VAE aqueous emulsion into a reaction kettle, adjust the reaction temperature to 75-80°C, set the speed of the magnetic stirrer to 800-1000 rpm, and stir for 30 minutes to obtain a packaging adhesive suitable for high-speed cigarette making equipment.

Citation Information

Patent Citations

  • Environmentally-friendly energy-saving cigarette adhesive and production method thereof

    CN102031075B

  • Super-high speed cigarette holder adhesive and preparation method thereof

    CN106753067A

  • Pressure sensitive adhesive layer and pressure sensitive adhesive sheet

    CN109504310A

  • Multipurpose water-based high-speed packaging adhesive and preparation method thereof

    CN117384570A

  • Aqueous solid adhesive and method of adhesion by using the same adhesive

    JP2003105305A